Comparism Of Thermal And Microwave Methods In Structural Modification Of Lumefantrine (International Journal of Engineering and Computer Science, 2017)
The three chlorine atoms on lumefantrine were replaced with 5-aminotetrazole using both thermal method (TM) and microwave method (MW). The products were characterized with GC-MS spectral analyses. The usual isotopic mass percentages of 35(75%) and 37(25%) of chlorine abundance in nature were absent in the product’s fragmentation peaks. Gas Chromatogram of the two methods showed that the percentage yield of the microwave method (MW) is about double that of the thermal method (TM).